MILITARY BASED LANDMINE DETECTION ROBOTIC VEHICLE - K., Nandakumar; R., Kesavan; N., Niyasudeen; M., Surendra Prasad; Y., Vaseem Akram (International Journal of Research -GRANTHAALAYAH, 2023)
A landmine is an explosive device which is concealed under the soil to destroy the enemy targets such as soldier, vehicle, tanks etc. Landmines in India are mostly planted in fields, forest, wells, water resources and energy production areas. The process of removing land mines from a soil is called Demining or mine clearance. In military operations, the deminig is done with help of the devices such as mine plows and blast waves. Sometimes specially trained animals also involved in the process of mine clearance. These existing method requires a lot of time to remove the landmine and which also involves loss of many lives during the demining process. To avoid the hazard the landmine detection robot is proposed which uses a ultrasonic sensor, metal detector and GSM module as a complementary tool for landmine detection. The robot is used to detects the position of the landmine and sends its GPS position to a web server through GSM.